Analysis Of Al-Qur'an And Hadith Materials as A Guide Of Life - Adona, Putri; Wulandari, Atika; Yahya, Muhamad; Rahman, Yenni (Jurnal Kajian dan Pengembangan Umat, 2024)
The Qur'an and Hadith are human guidelines, especially the Muslim,  which  have  been  left  by  Rasullullah  SAW  to  all  his ummah. The Qur'an is the word of God revealed to the Prophet Muhammad SAW, as a guide for humanity in organising their lives, in order to obtain happiness physically and mentally both in the world and in the hereafter. Moving on from this, in this study the author wants to analyse the material of the Qur'an and Hadith as a guide to life. The research method used is a qualitative method with  a  content  analysis  approach.  Where  the  main source is the Al-Qur'an Hadith Textbook for Madrasah Tsanawiyah published by the Ministry of Religion. After analysing the author found three subthemes in the textbook, including: 1) Understanding the Qur'an and Hadith as a guide to Muslim life, 2) The function of the Qur'an and Hadith as a guide to life, 3) The position of the Qur'an and Hadith as a guide to life. Furthermore, the author hopes that through this research new ideas will emerge for further research.